Hadith #3467 - Sunan Abi Dawud - Aabad bin al-Walid bin Khalid عباد بن الوليد بن خالد الغبري; Abu Sa'id al-Khudri; Atyh bin Sa'd bin Jnad'h عطية بن سعد بن جنادة; Muhammad bin 'Isa bin Hyan محمد بن عيسى بن حيان; Ziyad bin Khaythama al-Ja'fi زياد بن خيثمة الجعفي (Sunan Abi Dawud)
A man paid in advance for a palm-tree. It did not bear fruit that year. They brought their case for decision to the Prophet (ﷺ). He said: for which do you make his property lawful? He then said: Do not pay in advance for a palm-tree till they (the fruits) were clearly in good condition.
Grade: Da'if

Hadith #3977 - Sunan Abi Dawud - Abu Ja'far al-Nafaili عبد الله بن محمد أبو جعفر النفيلي الحران; Atyh bin Sa'd bin Jnad'h عطية بن سعد بن جنادة; Fdyl bin Mrzwq al-Aghr al-Rqashy فضيل بن مرزوق الأغر الرقاشي; Zuhayr bin Mua'wiya bin Hudayj زهير بن معاوية بن حديج (Sunan Abi Dawud)
The Prophet (ﷺ) read the verse: “We ordained therein for them: Life for life and eye for eye (an-nafsa bin-nafsi wal-‘aynu bil-‘ayn).
Grade: Da'if

Hadith #3986 - Sunan Abi Dawud - Aban bin Tghlb أبان بن تغلب; Abu Sa'id al-Khudri; Atyh bin Sa'd bin Jnad'h عطية بن سعد بن جنادة (Sunan Abi Dawud)
Ubayy ibn Ka’b made me read the following verse as the Messenger of Allah (ﷺ) made him read: “in a spring of murky water” (fi ‘aynin hami’atin) with short vowel a after h.
Grade: Sahih

Hadith #3997 - Sunan Abi Dawud - Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Abu Sa'id al-Khudri; Atyh bin Sa'd bin Jnad'h عطية بن سعد بن جنادة; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Uthman bin Muhammad (Sunan Abi Dawud)
A man whom the Prophet (ﷺ) made the following verse read informed me, or he was informed by a man whom a man made the following verse read through a man whom the Prophet (ﷺ) made the following verse read: “For, that day His chastisement will be such as none (else) can be inflicted (la yu’adhdhabu) Abu Dawud said: ‘Asim, al-A’mash, Talhah b. Musarrif, Abu Ja’far Yazid b. al-Qa’qa’, Shaibah b. Nassah, Nafi’ b. ‘Abd al-Rahman, ‘Abd Allah b. Kathir al-Dari, Abu ‘Amr b. al-
Grade: Hasan

Hadith #3998 - Sunan Abi Dawud - Abu Sa'id al-Khudri; Atyh bin Sa'd bin Jnad'h عطية بن سعد بن جنادة; Muhammad bin Khazim al-Darir محمد بن خازم أبو معاوية الضرير; Zayd bin Akhzm زيد بن أخزم (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) related a tradition in which he mentioned the words “Jibril and Mikal” and he pronounced them “Jibra’ila wa Mika’ila.” Abu Dawud said: Khalaf said: I did not put the pen aside from writing letters (huruf) for forty years: nothing tired me (or made me incapable of writing), even Jibril and Mika’il did not tire me.
Grade: Da'if

Hadith #4342 - Sunan Abi Dawud - Abu Sa'id al-Khudri; Atyh bin Sa'd bin Jnad'h عطية بن سعد بن جنادة; Isra'il bin Yonus bin Abi Ishaq إسرائيل بن يونس بن أبي إسحاق; Muhammad bin ''Aabadh محمد بن عبادة; Muhammad bin Jahada محمد بن جحادة; Yazid bin Harun يزيد بن هارون (Sunan Abi Dawud)
The Prophet (ﷺ) said: How will you do when that time will come? Or he said: A time will soon come when the people are sifted and only dregs of mankind survive and their covenants and guarantees have been impaired and they have disagreed among themselves and become thus, interwining his fingers. They asked: What do you order us to do, Messenger of Allah? He replied: Accept what you approve, abandon what you disapprove, attend to your own affairs and leave alone the affairs of the generality. Ab
Grade: Sahih

Hadith #476 - Jami' al-Tirmidhi - Abu Sa'id al-Khudri; Atyh bin Sa'd bin Jnad'h عطية بن سعد بن جنادة; Fdyl bin Mrzwq al-Aghr al-Rqashy فضيل بن مرزوق الأغر الرقاشي; Muhammad bin Rabi'ya al-Klaby محمد بن ربيعة الكلابي; Ziyad bin Ayoub - Dulwiyya زياد بن أيوب بن زياد دلويه (Jami' al-Tirmidhi)
“The Prophet would pray Ad-Duha until we would say: ‘He will not leave it.’ And he would leave it until we would say: ‘He will not pray it.'”
Grade:

Hadith #2566 - Jami' al-Tirmidhi - Abu Sa'id al-Khudri; Ammar bin Muhammad al-Thawri عمار بن محمد الثوري أبو اليقظان الكوفي; Atyh bin Sa'd bin Jnad'h عطية بن سعد بن جنادة; Muhammad bin Hatm bin Sulaiman محمد بن حاتم بن سليمان الزمي (Jami' al-Tirmidhi)
“There are three whom Allah, the Mighty and Glorious, loves: A man who stood at night reciting the Book of Allah; a man who spent in charity with his right hand, concealing it”- it seems to me he said “from his left hand”- “and a man who was in a small expedition while his companions were decimated, yet he faced enemy.” Another chain reports a similar narration.
Grade:

Hadith #3103 - Jami' al-Tirmidhi - Atyh bin Sa'd bin Jnad'h عطية بن سعد بن جنادة; Fdyl bin Mrzwq al-Aghr al-Rqashy فضيل بن مرزوق الأغر الرقاشي; ibn Umar; Muhammad bin Hmyd bin Hyan محمد بن حميد بن حيان; N'ym bin Mysrh نعيم بن ميسرة (Jami' al-Tirmidhi)
“From ‘Ubaid bin As-Sabbaq, that Zaid bin Thabit narrated to him, he said: ‘Abu Bakr As-Siddiq sent for me – (regarding) those killed at Al-Yamamah – and ‘Umar bin Al-Khattab was with him. He (Abu Bakr) said: “‘Umar came to me and said: The fighting inflicted many casualties among the reciters of the Qur’an on the Day of Al-Yamamah, and I fear that there will be more casualties among the reciters in other parts of the land, such that much of the Qur’an may be lost. In my view
Grade:

Hadith #3466 - Jami' al-Tirmidhi - Abu Sa'id al-Khudri; Atyh bin Sa'd bin Jnad'h عطية بن سعد بن جنادة; Matruf bin Tarayf al-Harithi مطرف بن طريف; Muhammad bin Yahya bin Abi 'Umar محمد بن يحيى بن أبي عمر العدني; Sufyan bin 'Uyaynah سفيان بن عيينة (Jami' al-Tirmidhi)
The Messenger of Allah (ﷺ) said: “There are two statements that are light on the tongue, heavy on the Scale, and beloved to Ar-Raḥmān: “Glory is to Allah and the praise; Glory is to Allah, the Magnificent. (Subḥān Allāhi wa biḥamdih, Subḥān Allāhil-Aẓīm)”
Grade:

Hadith #101 - Sunan Ibn Majah - Abu Sa'id al-Khudri; Ali bin Muhammad bin Ishaq al-Tanafasi علي بن محمد بن إسحاق الطنافسي; Atyh bin Sa'd bin Jnad'h عطية بن سعد بن جنادة; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Ibn Majah)
She poured water for Abu Qatadah to perform ablution. A cat came and drank the water, and he tilted the vessel for it. She started looking at it (in surprise) and he said: “O daughter of my brother, do you find it strange? The Messenger of Allah said: ‘They (cats) are not impure, they are of those who go around among you.'”
Grade:

Hadith #1183 - Sunan Ibn Majah - Atyh bin Sa'd bin Jnad'h عطية بن سعد بن جنادة; Baqiyya bin al-Walid bin Sa'aid بقية بن الوليد بن صائد; Hajjaj bin Artah حجاج بن أرطاة; ibn Abbas; Muhammad bin Yahya bin Hiban محمد بن يحيى بن حبان; Yazid bin Abd Rbh يزيد بن عبد ربه الزبيدي (Sunan Ibn Majah)
“When Ka’b was dying, Umm Bishr bint Bara’ bin Ma’rur came to him and said: ‘O Abu ‘Abdur-Rahman! If you meet so-and-so, convey Salam to him from me.’ He said: ‘May Allah forgive you, O Umm Bishr! We are too busy to think of that.’ She said: ‘O Abu ‘Abdur-Rahman! Did you not hear the Messenger of Allah (ﷺ) say: “The souls of the believers are in green birds, eating from the trees of Paradise”?’ He said: ‘Yes.’ She said: ‘That is what I mean.’”
Grade:

Hadith #1964 - Sunan Ibn Majah - Abu Sa'id al-Khudri; Atyh bin Sa'd bin Jnad'h عطية بن سعد بن جنادة; Muhammad bin Yazid Abu Hisham al-Rafa'i محمد بن يزيد أبو هشام الرفاعي; Yahya bin Yaman al-Jly يحيى بن يمان العجلي (Sunan Ibn Majah)
“I used to sell dates in the marketplace, and I would say: ‘This was such and such an amount (when I bought it).’ I Would give the purchaser a specific amount of dates according to the way it had been measured for me, and take my profit. Then I began to have some doubts about that, so I asked the Messenger of Allah (ﷺ), and he said: ‘When you name the amount, measure it in front of the purchaser.”‘
Grade:

Hadith #3797 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Abu Sa'id al-Khudri; Atyh bin Sa'd bin Jnad'h عطية بن سعد بن جنادة; Bakr bin 'Abdur Rahman bin 'Abdullah بكر بن عبد الرحمن بن عبد الله بن عيسى; Isa bin al-Mukhtar عيسى بن المختار بن عبد الله بن عيسى (Sunan Ibn Majah)
“There will be among my nation collapsing of the earth, transformations, and Qadhf.”
Grade:

Hadith #4143 - Sunan Ibn Majah - Abu Sa'id al-Khudri; al-Qasim bin Zakaria bin Dinar القاسم بن زكريا بن دينار القرشي; Atyh bin Sa'd bin Jnad'h عطية بن سعد بن جنادة; Isra'il bin Yonus bin Abi Ishaq إسرائيل بن يونس بن أبي إسحاق; Muhammad bin ''Aabadh محمد بن عبادة; Muhammad bin Jahada محمد بن جحادة; Yazid bin Harun يزيد بن هارون (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) said: ‘By the One in whose Hand is my soul! You will not enter Paradise until you believe, and you will not (truly) believe until you love one another. Shall I not tell you of something which, if you do it, you will love one another? Spread the greetings of Salam amongst yourselves.'”
Grade: